Future Heat and Electricity Generation from Bertoni Plant in Morocco - Mahdavi, Meisam; Jurado, Francisco; Schmitt, Konrad; Ramos, Ricardo Alan Verdu [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Morocco's energy sector heavily depends on fossil fuel imports to meet a large portion of the country's primary energy demand. However, costly energy imports along with the growing national energy need, pushed Morocco to look for alternative energy resources. One of these alternatives is Stevia rebaudiana (Bertoni), a native plant in Paraguay. This plant is now an important agricultural crop for the production of a high-potency natural sweetener in Canada, the USA, Switzerland, Germany, and France. Nevertheless, it is not produced in Morocco, but research conducted on the crop yield of this agricultural plant shows its great potential for cultivation in Morocco. The dry leaf yield of Bertoni depends on its variety and cultivated region. Stevia has great potential to be a commercial crop for biological sweeteners and energy production. Therefore, in the present paper, the potential of heat and electric energy generated by Bertoni's dry leaf in various regions of Morocco with different weather conditions are studied. The results show that Bertoni's dry leaves are good biomass resources for energy generation in the Moroccan regions of Berkane, Larache, Marrakech, Rabat, and Sefrou.
Keywords: Agricultural crops; Bertoni; electricity; heat energy generation; Morocco